Mothers' psychological contracts: Does supervisor breach explain intention to leave the organization? - Botsford Morgan, Whitney; King, Eden B. (Human Resource Management, 2012)
AbstractRecent evidence suggests mothers with infants are leaving the workforce (Cohany & Sok, 2007; Johnson, 2007), but research has not yet clarified why mothers make such a decision. The current research proposes that mothers form psychological contracts including content related to family that supervisors do not fulfill, resulting in intention to leave the organization. In a study of first‐time mothers, participants reported experiencing contract breach. Findings also suggested supervisors may have an opportunity to control the outcomes of breach and retain mothers by effectively managing perceptions of fair treatment (i.e., interactional justice). This is the first empirical research to indicate that mothers' intentions to leave depend on fulfillment of their psychological contracts related to family and fair treatment from their supervisor.